Fasting‐induced liver GADD45β restrains hepatic fatty acid uptake and improves metabolic health - Jessica Fuhrmeister; Annika Zota; Tjeerd P Sijmonsma; Oksana Seibert; Şahika Cıngır; Kathrin Schmidt; Nicola Vallon; Roldan M de Guia; Katharina Niopek; Mauricio Berriel Diaz; Adriano Maida; Matthias Blüher; et al. (EMBO Molecular Medicine)
Abstract Recent studies have demonstrated that repeated short‐term nutrient withdrawal (i.e. fasting) has pleiotropic actions to promote organismal health and longevity. Despite this, the molecular physiological mechanisms by which fasting is protective against metabolic disease are largely unknown. Here, we show that, metabolic control, particularly systemic and liver lipid metabolism, is aberrantly regulated in the fasted state in mouse models of metabolic dysfunction. Liver transcript assays between lean/healthy and obese/diabetic mice in fasted and fed states uncovered “growth arrest and DNA damage‐inducible” GADD45β as a dysregulated gene transcript during fasting in several models of metabolic dysfunction including ageing, obesity/pre‐diabetes and type 2 diabetes, in both mice and humans. Using whole‐body knockout mice as well as liver/hepatocyte‐specific gain‐ and loss‐of‐function strategies, we revealed a role for liver GADD45β in the coordination of liver fatty acid uptake, through cytoplasmic retention of FABP1, ultimately impacting obesity‐driven hyperglycaemia. In summary, fasting stress‐induced GADD45β represents a liver‐specific molecular event promoting adaptive metabolic function.